Can dynamic in vitro digestion systems mimic the physiological reality?. Issue 10 (31st May 2019) - Dupont, D.; Alric, M.; Blanquet-Diot, S.; Bornhorst, G.; Cueva, C.; Deglaire, A.; Denis, S.; Ferrua, M.; Havenaar, R.; Lelieveld, J.; Mackie, A. R.; Marzorati, M.; et al.
ABSTRACT: During the last decade, there has been a growing interest in understanding the fate of food during digestion in the gastrointestinal tract in order to strengthen the possible effects of food on human health. Ideally, food digestion should be studied in vivo on humans but this is not always ethically and financially possible. Therefore simple static in vitro digestion models mimicking the gastrointestinal tract have been proposed as alternatives to in vivo experiments but these models are quite basic and hardly recreate the complexity of the digestive tract. In contrast, dynamic models that allow pH regulation, flow of the food and injection in real time of digestive enzymes in the different compartments of the gastrointestinal tract are more promising to accurately mimic the digestive process. Most of the systems developed so far have been compared for their performances to in vivo data obtained on animals and/or humans. The objective of this article is to review the validation towards in vivo data of some of the dynamic digestion systems currently available in order to determine what aspects of food digestion they are able to mimic. Eight dynamic digestion systems are presented as well as their validation towards in vivo data. Advantages and limits of each simulator is discussed. This is the result of a cooperative international effort made by some of the scientists involved in Infogest, an international network on food digestion